2011
DOI: 10.1002/chem.201001743
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Organic Solvents Revisited by Using the COSMO‐RS Approach

Abstract: A new approach for the classification of solvents is proposed, based solely on the solvent molecular structure and relying on the "COnductor-like Screening MOdel for Real Solvents" (COSMO-RS), in which solvents are considered in their liquid state. This approach provides an a priori classification without requiring the knowledge of any experimental data. The theoretical descriptors of the proposed classification are generated through the analysis of the COSMO-RS σ-potential profiles. By applying a two-step sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 40 publications
0
40
0
3
Order By: Relevance
“…19 These differences are mainly due to the fact that descriptions of hydrogen bond and nitrogen atom are more accurate with the new version of COSMOtherm. The accuracy improvement of nitrogen atoms description led to important differences of sigma potential of nitrogen-containing molecules, especially for trisubstituted amines (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 These differences are mainly due to the fact that descriptions of hydrogen bond and nitrogen atom are more accurate with the new version of COSMOtherm. The accuracy improvement of nitrogen atoms description led to important differences of sigma potential of nitrogen-containing molecules, especially for trisubstituted amines (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…19 This procedure involves a Principal Component Analysis (PCA)/k-means classification applied to the socalled "σ-potentials" curves calculated via the COSMO-RS approach. A major advantage of this method is that any new solvent can be positioned within this classification thanks to its σ-potential calculated with COSMO-RS and converted into the coordinates into the new space defined by the PCA.…”
Section: Introductionmentioning
confidence: 99%
“…COSMO-RS combines quantum chemical considerations (COSMO) and statistical thermodynamics (RS) to determine and predict thermodynamic properties without experimental data. (Benazzouz, Moity, Pierlot, Molinier, & Aubry, 2014;Durand, Molinier, Kunz & Aubry, 2011;Garcia-chavez, Hermans, Schuur, & de Haan, 2012;Klamt, 2003;Zhou, Qi, & Sundmacher, 2014).…”
Section: Computational Methods: Software Cosmo-rsmentioning
confidence: 98%
“…This approachd oes not provide quantitative estimates of solubility.The theoretical COSMO-RS calculations introduce ar eference solute (only defined by its surface charge), and the data generatedc an be used to estimate the thermodynamic properties of liquidsa nd to predict equilibria and relative solvation energies on aq uantitative basis. [31] Instead, the assessment was continued with alternative measures of solvent polarity to give greater significance to nonspecific solvent-solute interactions (as obtained experimentally). Differences in hydrogen bond character shown throughC OSMO-RS theory indicate possible limitations for Cyrene and the Cygnet solvents in applicationst hat depend currentlyo ne ither NMP or DCM, respectively.H owever,e xperimental studies using Cyrene as as olventh ave shown it to be comparable to NMP in many respects.…”
Section: Model 2: Cosmo-rsmentioning
confidence: 99%